2001
DOI: 10.1002/app.1357
|View full text |Cite
|
Sign up to set email alerts
|

Molecular weight effect on antimicrobial activity of chitosan treated cotton fabrics

Abstract: ABSTRACT:The effect of the molecular weight of chitosan on antimicrobial activity was investigated using three chitosans of different molecular weights [1800 (water soluble), 100,000, and 210,000] and similar degrees of deacetylation (86 -89%). Cotton fabrics were treated with chitosan by the pad-dry-cure method. The molecular weight dependence of the antimicrobial activity of chitosan was more pronounced at a low treatment concentration. Chitosans with molecular weight of 100,000 and 210,000 effectively inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
62
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(69 citation statements)
references
References 11 publications
6
62
0
1
Order By: Relevance
“…This resulted in a structure in which most of the hydrophilic segment -NH 2 , which are effective in antimicrobial activity are outwardly aligned at the surface of the structure. This is in line with Shin [26] who studied the molecular weight effect on antimicrobial activity of chitosan treated cotton fabrics. He found that chitosan with molecular weight 1800 is more than 10 times as effective when treated on polypropylene fabric than in cotton fabric in terms of antimicrobial activity.…”
Section: Antimicrobial Propertiessupporting
confidence: 86%
“…This resulted in a structure in which most of the hydrophilic segment -NH 2 , which are effective in antimicrobial activity are outwardly aligned at the surface of the structure. This is in line with Shin [26] who studied the molecular weight effect on antimicrobial activity of chitosan treated cotton fabrics. He found that chitosan with molecular weight 1800 is more than 10 times as effective when treated on polypropylene fabric than in cotton fabric in terms of antimicrobial activity.…”
Section: Antimicrobial Propertiessupporting
confidence: 86%
“…The results showed that the molecular weight of the CS L using the buffer solution only decreased by 31%, whereas the decrease was 79% for CS H . The percent reduction was calculated following the method reported by Shin et al (2001). Conversely, Choi and coworkers (1999) reported a 91% decrease in the molecular weight of 1% chitosan (molecular weight 1.1x10 6 ) in acetic acid after autoclaving for 15 minutes at 121 o C. The infrared spectra of chitosan, PAA and complex (PAA-CS) are shown in Figure 1 for comparative purposes.…”
Section: Resultsmentioning
confidence: 99%
“…Literatürde yapılan çalışmalarda kitosan polimeri ile işlem görmüş kumaşların gram pozitif ve gram negatif bakterilere karşı geniş spektrum antibakteriyel aktivite ve antifungal etki göster-diği, ancak bu etkinin farklı bakteri türü için kitosanın molekül ağırlığı ve konsantrasyonuna bağlı olarak değiştiği ifade edilmektedir. Genellikle molekül ağırlığı arttıkça daha düşük konsantrasyonlarda antibakteriyel aktivite sağlandığı sonucuna ulaşılmıştır [16][17][18]. Öte yandan Jelatin/arap zamkı/nano çinko oksit duvarlı mikrokapsül örneğinin antibakteriyel aktiviteye sahip olması ise duvar yapısına ilave edilen nano çinko oksit varlığı ile açıklanabilir.…”
Section: Antibakteriyel Aktivite Tayiniunclassified